Synthesis and Characterization of some New Amic acid and Imides and study the Biological Activity - Salwa Abd Al-Satar Jabbar (Tikrit Journal of Pure Science, 2023)
This study includs the synthesis of some new Amic acid and Imides, starting from the esters [S1] of Terephthalic acid which then converted to its hydrazide [S2] then to amic acid derivatives [S3-S7] and finally with imides [S8-S12]. Preparing of ester [S1] by usual esterification of terephthalic acid with absolute ethanol in acidic medium, then has converted to its hydrazide [S2] by reacting it with hydrazine hydrate. The amic acid derivatives [S3-S7] have been synthesized by the reaction of hydrazide [S2] with anhydrides (2,3-dimethyl malic anhydride, 3-nitro phthalic anhydride, hexahydro phthalic anhydride, Diphenic anhydride, tetra Phenyl phthalic anhydride) in diethyl ether. Imides [S8-S12] were also synthesized by cyclization of amic acids derivatives using acetic acid anhydride and anhydrous sodium acetate. The synthesized compounds were identified by spectral methods UV, FT-IR and H1- NMR beside melting point and the purity was determined using (TLC) and some of its physical properties were measured. Some of these compounds were tested against four strains of bacteria (E. coli, P. ariginosa, S. aurous and S. pyogenes)